Cassava - Waisundara, Viduranga (IntechOpen, 2018)
Cassava is a staple food for many nations owing to its resilience for growth under various climatic conditions. It is a good source of carbohydrates and is the third largest source of food carbohydrates in the tropics, after rice and maize. This book focuses on the morphological traits and nutritive properties of cassava and its production processes, postharvest techniques and diseases that affect the growth of the crop. Given its extensive usage and market value, it is one of the agricultural produces for which many biotechnological interventions have been applied for ascertaining food security. It is hoped that readers will gain knowledge on cassava as well as use some of the techniques mentioned herein for improvement of the production of the crop.